Status of Non-Government Public Libraries in Bangladesh - Shuva, Nafiz Zaman; Akter, Rowshon (Eastern Librarian, 2012)
Public libraries are very important social organizations in building knowledge based society. There are two types of public libraries in Bangladesh i.e. Government public libraries and Non-Government public libraries. This article concentrates on the status of Non-Government public libraries in Bangladesh. There is very few literature on Non-Government public libraries in Bangladesh. Currently there are 972 Non-Government public libraries running in Bangladesh. In gathering data on Non-Government public libraries in Bangladesh, the Directory of Non-Government Public Libraries published by National Book Centre is considered. A Focus Group Discussion (FGD) has been conducted to acquire comprehensive information about the status of Non-Government public libraries in Bangladesh. Eventually some problems of Non-Government public libraries have been addressed and as remedial measures a number of recommendations have been put forward by the authors. DOI: http://dx.doi.org/10.3329/el.v23i1.12119 Eastern Librarian Vol.23(1) 2012 pp.91-104